Nucleotide Sequencing and Identification of Some Wild Mushrooms - Sudip Kumar Das; Aninda Mandal; Animesh K. Datta; Sudha Gupta; Rita Paul; Aditi Saha; Sonali Sengupta; Priyanka Kumari Dubey (The Scientific World Journal)
The rDNA-ITS (Ribosomal DNA Internal Transcribed Spacers) fragment of the genomic DNA of 8 wild edible mushrooms (collected from Eastern Chota Nagpur Plateau of West Bengal, India) was amplified using ITS1 (Internal Transcribed Spacers 1) and ITS2 primers and subjected to nucleotide sequence determination for identification of mushrooms as mentioned. The sequences were aligned using ClustalW software program. The aligned sequences revealed identity (homology percentage from GenBank data base) of Amanita hemibapha [CN (Chota Nagpur) 1, % identity 99 (JX844716.1)], Amanita sp. [CN 2, % identity 98 (JX844763.1)], Astraeus hygrometricus [CN 3, % identity 87 (FJ536664.1)], Termitomyces sp. [CN 4, % identity 90 (JF746992.1)], Termitomyces sp. [CN 5, % identity 99 (GU001667.1)], T. microcarpus [CN 6, % identity 82 (EF421077.1)], Termitomyces sp. [CN 7, % identity 76 (JF746993.1)], and Volvariella volvacea [CN 8, % identity 100 (JN086680.1)]. Although out of 8 mushrooms 4 could be identified up to species level, the nucleotide sequences of the rest may be relevant to further characterization. A phylogenetic tree is constructed using Neighbor-Joining method showing interrelationship between/among the mushrooms. The determined nucleotide sequences of the mushrooms may provide additional information enriching GenBank database aiding to molecular taxonomy and facilitating its domestication and characterization for human benefits.